Guanidine Affects Differentially the Twitch Response of Diaphragm, Extensor Digitorum Longus and Soleus Nerve-Muscle Preparations of Mice - Ferrari, Rosana [UNESP]; Rodrigues-Simioni, Lea; da Cruz Hoefling, Maria Alice (Mdpi Ag, 2012)
Guanidine has been used with some success to treat myasthenia gravis and myasthenic syndrome because it increases acetylcholine release at nerve terminals through K+, Na+ and Ca2+ channels-involving mechanisms. Currently, guanidine derivatives have been proposed for treatment of several diseases. Studies aimed at providing new insights to the drug are relevant. Experimentally, guanidine (10 mM) induces on mouse phrenic nerve-diaphragm (PND) preparations neurotransmission facilitation followed by blockade and a greatest secondary facilitation after its removal from bath. Herein, we hypothesized that this peculiar triphasic response may differ in muscles with distinct twitch/metabolic characteristics. Morphological alterations and contractile response of PND, extensor digitorum longus (EDL) and soleus (SOL) preparations incubated with guanidine (10 mM) for 15, 30, 60 min were analyzed. Guanidine concentrations of 5 mM (for PND and EDL) and 1 mM (for EDL) were also tested. Guanidine triphasic effect was only observed on PND regardless the concentration. The morphological alterations in muscle tissue varied along time but did not impede the PND post-wash facilitation. Higher doses (20-25 mM) did not increase EDL or SOL neurotransmission. The data suggest a complex mechanism likely dependent on the metabolic/contractile muscle phenotype; muscle fiber types and density/type of ion channels, sarcoplasmic reticulum and mitochondria organization may have profound impact on the levels and isoform expression pattern of Ca2+ regulatory membrane proteins so reflecting regulation of calcium handling and contractile response in different types of muscle.
Keywords: neuromuscular transmission; transmitter release; contractility; skeletal muscle